Improved Yellow Phosphors for Solid State White Lighting: An Experimental Study - Yadav , P. J. (Technological Innovation in Engineering Research Vol. 3, 2022)
Blue chips covered with yellow emitting phosphor are used in the majority of commercial white LED lamps. YAG: Ce3+ phosphor is coated on a blue chip to obtain white light. Despite its commercial success, there are a number of flaws, such as the "halo effect," poor color rendition, and so on. So many attempts have been devoted in recent years to improve the performance of LED lamps. These may be classified as 1> finding a replacement for YAG: Ce and 2> improving the performance of YAG: Ce. When the conversion phosphor is situated near the LED chip, its thermal behavior is of great importance.